5PSQ-099 Impact of robotics on patient safety and productivity. (March 2019) - Al Nemari, M; Zayed, E; Bin Dous, A; Malhani, A; Al Banyan, N; Al Rassan, A; Faqehi, M; Sharma, P; Al Faadhel, Am; Al Sarheed, A; Gashi, M
Abstract : Background: Automated dispensing machines are centralised medication distribution systems that provide computer-controlled storage, dispensing and tracking of medications. It is recommended as a potential mechanism to improve efficiency and patient safety. It has been proven that automation enhances the efficiency of medication distribution and its capability to reduce medication errors, increase patient safety, streamline hospital pharmacy operations and increase accuracy. Purpose: To find out the effect of automated dispensing machines versus normal workflow on turnaround time (TAT), medication error (MER) reduction and workload on staff involved in inpatient unit dose. Material and methods: Six sigma approaches were used to study the medication process before and after automation. Implementation of automated dispensing machines at the main hospital was in December 2013, medications (total 95 136 units processed) were received through automation, TAT, MER and overtime of staff concerned were measured during 2014 and 2015. Same parameters were considered retrospectively for the period of January–November 2013, where medications (total 62 502 units processed) were packaged, prepared and labelled manually. Data were collected after implementing automation and compared to the pre-available data. Results: By comparing manual and automated medication packaging, storage, dispensing and labelling, we found a vast reduction in TAT from 56 min to 17 min which equals 69%. In addition, a dramatic decrease in preparation time was obtained, where preparing 10 items by automation was instant and did not take more than 1 min, while the manual preparation time was 17 min. Overtime reduction was valuable as well, where the pharmacy was able to achieve a 66% decrease in overtime (from 889 to 302 hours). MER was also reduced by 100%, which had a positive impact on safety as a result of the accurate dispensing process. Conclusion: The implementation of automated dispensing machines and centralised medication distribution systems has a significantly positive impact on patient safety due to a reduction in medication errors, hence patient safety. The use of automation in healthcare has the potential to increase the quality of patient care in the hospital setting. Automation not only confirms the five rights of medication for each patient, but also allows healthcare professionals to perform tasks that improve patient care in other ways. References and/or acknowledgements: No conflict of interest.